(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This paper aims to discuss the significance of Infopreneurship as a future academic course and job option for university graduates. Infopreneurs can be defined as an entrepreneur who recognize opportunities and utilize information, products and services available for creating an information-based business. This paper covers the importance of infoproneurship, roles and skills, challenges and curriculum suitability of infopreneurship.